Lateral hypothalamic GAD65 neurons are spontaneously firing and distinct from orexin- and melanin-concentrating hormone neurons - Karnani, Mahesh M (Blackwell Science Inc, 2013)
GABAergic neurons are vital for brain function. Their neurochemical and electrical features have been classically characterized in the cortex, but in the lateral hypothalamic area (LHA), such knowledge is lacking, despite the emerging roles of LHA GABAergic cells in feeding and sleep. We used GAD65-GFP transgenic mice, developed for studies of cortical GABAergic cells, to determine fundamental properties of LHA GAD65 neurons, and compare them to ‘classical’ GABAergic cell types of the cortex, and to previously described classes of LHA cells. Whole-cell patch-clamp recordings in acute brain slices revealed that, unlike cortical GABAergic interneurons, LHA GAD65 neurons were intrinsically depolarized and fired action potentials spontaneously. Similar to cortical GABAergic cells, LHA GAD65 cells fell into four major subtypes based on evoked firing: fast spiking, late spiking, low threshold spiking and regular spiking. Three-dimensional reconstructions of biocytin-filled neurons, performed after the patch-clamp analysis, did not reveal striking morphological differences between these electrophysiological subtypes. Peptide transmitters expressed in known classes of LHA projection neurons, namely melanin-concentrating hormone (MCH) and hypocretin/orexin (hcrt/orx), were not detected in LHA GAD65 cells. Approximately 40% of LHA GAD65 cells were directly inhibited by physiological increases in extracellular glucose concentration. Glucose inhibition was most prevalent in the fast spiking subpopulation, although some glucose-responsive neurons were found in each electrophysiological subpopulation. These results suggest that LHA GAD65 neurons are electrically different from ‘classical’ GABAergic neurons of the cortex, are neurochemically distinct from LHA hcrt/orx and MCH cells, but partly resemble hcrt/orx cells in their glucose responses.